2009
DOI: 10.1007/s12098-009-0010-8
|View full text |Cite
|
Sign up to set email alerts
|

‘Thinfat’ phenotype in newborns

Abstract: Despite being small, truncal adiposity was present in Davangere neonates confirming the 'thinfat' phenotype. The role of consanguinity in other words, the role of genes, is important in determining this 'thinfat' phenotype in newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…[3334] These features appear to be present from birth as Indian neonates tend to have increased body fat compared to their Caucasians despite lower birth weights. [33–35] These unique features led to the coining of the term ‘Thin-Fat phenotype’[33] or ‘Asian Indian Phenotype′. [35]…”
Section: Methodsmentioning
confidence: 99%
“…[3334] These features appear to be present from birth as Indian neonates tend to have increased body fat compared to their Caucasians despite lower birth weights. [33–35] These unique features led to the coining of the term ‘Thin-Fat phenotype’[33] or ‘Asian Indian Phenotype′. [35]…”
Section: Methodsmentioning
confidence: 99%
“…However, under the "thrifty phenotype hypothesis" visceral adiposity in neonates with intrauterine growth restriction may have advantages in the neonatal period but this could persist into adulthood life. Some recent studies in India have demonstrated a higher visceral adiposity and a lower birth weight in Indians neonates compared with English newborns; this phenotype was described as muscle thin but "thinfat" [17,18]. All these findings are in accordance with developing origins of health and diseases.…”
Section: Discussionmentioning
confidence: 78%
“…In a developing country like India, Widal test has been used extensively in the serodiagnosis of typhoid fever. Fourfold rise of the antibody titre in paired sera are often is considered as diagnostic of typhoid fever (Kulkarni, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…R syamlal et al, and Kulkarni et al, revealed that a single Widal test, in association with relevant clinical findings ,can still be used as a useful diagnostic tool for typhoid fever (Kulkarni et al, 1994;Shanthi et al, 2012). Among the patients included in this study,62.3% cases are in the range of age 11-20 years followed by 29.7% in the age group of 21-30 years for TO and 52.9% for TH in age group 11-20 years and ,this may indicate that most Salmonella infections occur mainly in young adults.…”
Section: Resultsmentioning
confidence: 99%